2018
DOI: 10.1038/s41598-018-29730-x
|View full text |Cite
|
Sign up to set email alerts
|

Types of tobacco consumption and the oral microbiome in the United Arab Emirates Healthy Future (UAEHFS) Pilot Study

Abstract: Cigarette smoking alters the oral microbiome; however, the effect of alternative tobacco products remains unclear. Middle Eastern tobacco products like dokha and shisha, are becoming globally widespread. We tested for the first time in a Middle Eastern population the hypothesis that different tobacco products impact the oral microbiome. The oral microbiome of 330 subjects from the United Arab Emirates Healthy Future Study was assessed by amplifying the bacterial 16S rRNA gene from mouthwash samples. Tobacco co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
68
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 57 publications
14
68
2
Order By: Relevance
“…Consistent with previous several reports, we detected a signi cant taxonomic difference between smoker and nonsmoker groups, but no signi cant differences in terms of microbial diversity and richness as shown in gure S3 [25][26][27]. Interestingly, a previous study conducted in the UAE determined only marginal signi cance of the overall oral microbial differences in smokers compared with non-smokers, underscoring the geographic and ethnic contribution [15]. However, our nding was not consistent with other groups reporting signi cant change in richness and diversity [28,29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous several reports, we detected a signi cant taxonomic difference between smoker and nonsmoker groups, but no signi cant differences in terms of microbial diversity and richness as shown in gure S3 [25][26][27]. Interestingly, a previous study conducted in the UAE determined only marginal signi cance of the overall oral microbial differences in smokers compared with non-smokers, underscoring the geographic and ethnic contribution [15]. However, our nding was not consistent with other groups reporting signi cant change in richness and diversity [28,29].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, smoking contributes to the alteration in the oxygen tension of the oral and upper gastrointestinal microenvironment that encourages persistence of microaerophilic bacteria replacing the commensal bene cial species [12,13]. Previous studies have shown an increased prevalence of the genera Atopobium, Campylobacter, and Prevotella among smokers and selective depletion of certain phyla including Proteobacteria [12,[14][15][16] .Thus, tobacco smoking creates a unique dysbiotic environment in the oral cavity in uencing the microbiota composition that has a far reaching consequences in the local and systemic health of the host [8]. In this study, we intend to decipher our understanding of the oral microbiota's composition and its alteration due to tobacco smoking and smoking severity (nicotine dependence level).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, and in line with the results of A. T. M. Saeb et al (13), in our study, Gammaproteobacteria abundance was higher but not significant in the healthy individuals, whereas Betaproteobacteria was significantly higher in the diabetes group (p=0.03). An interesting result was that the TG5 genus, belonging to the Synergistia class, the only one that showed significant differences between groups, has been related to periodontitis (19), failed implants (33) and smoking habits (34, 35). In our findings, unexpectedly, this taxon was found in 72% of the healthy samples against only 9% of diabetes individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have also demonstrated the strong inhibitory effect of smoking in Neisseria growth [54]. Other genera were enriched in smokers including Bacteroides [55]. Treponema [14].…”
Section: Discussionmentioning
confidence: 99%
“…Treponema [14]. TG5 and Mycoplasma [55]. especially Mycoplasma may be synergize with smoking to produce the pro-inflammatory effects [56].…”
Section: Discussionmentioning
confidence: 99%